Single-step fabrication of electrodes with controlled nanostructured surface roughness using optically-induced electrodeposition. (9th January 2018) - Liu, N; Li, M; Liu, L; Yang, Y; Mai, J; Pu, H; Sun, Y; Li, W J
Abstract: The customized fabrication of microelectrodes from gold nanoparticles (AuNPs) has attracted much attention due to their numerous applications in chemistry and biomedical engineering, such as for surface-enhanced Raman spectroscopy (SERS) and as catalyst sites for electrochemistry. Herein, we present a novel optically-induced electrodeposition (OED) method for rapidly fabricating gold electrodes which are also surface-modified with nanoparticles in one single step. The electrodeposition mechanism, with respect to the applied AC voltage signal and the elapsed deposition time, on the resulting morphology and particle sizes was investigated. The results from SEM and AFM analysis demonstrated that 80–200 nm gold particles can be formed on the surface of the gold electrodes. Simultaneously, both the size of the nanoparticles and the roughness of the fabricated electrodes can be regulated by the deposition time. Compared to state-of-the-art methods for fabricating microelectrodes with AuNPs, such as nano-seed-mediated growth and conventional electrodeposition, this OED technique has several advantages including: (1) electrode fabrication and surface modification using nanoparticles are completed in a single step, eliminating the need for prefabricating micro electrodes; (2) the patterning of electrodes is defined using a digitally-customized, projected optical image rather than using fixed physical masks; and (3) both the fabrication and surface modification processes are rapid, and the entire fabrication process only requires less than 6 s.